PENGARUH BEBAN PAJAK, INTANGIBLE ASSET, DAN KEPEMILIKAN ASING TERHADAP TRANSFER PRICING - Rizqy Patahillah; Lia Ira Sahara (Jurnal Nusa Akuntansi, 2026)
This study aims to analyze and empirically demonstrate the influence of Tax Burden, Intangible Asset, and Foreign Ownership on Transfer Pricing. This quantitative associative study utilizes secondary data collected from the Indonesia Stock Exchange website and company websites. The population of this study was non-cyclical consumer sector companies listed on the Indonesia Stock Exchange between 2020 and 2024. The sample selection procedure used purposive sampling, with only 43 companies meeting the criteria. The data analysis technique used panel data regression analysis using E-Views 13. The results of this study indicate that tax burden, intangible assets, and foreign ownership simultaneously influence transfer pricing. Partially, tax burden and intangible assets have no effect on transfer pricing, while foreign ownership does.